Intraligamentary anesthesia An alternative to inferior alveolar nerve block for the extraction to teeth - Dumbrigue, Herman B.
This study was undertaken to compare the intraligamentary technique of anesthetic administration with the classically administered inferior alveolar nerve block in terms of rapidity of onset, profoundness of anesthesia obtained, and patient preference. Intraligamentary and block injections using citanest with octapressin were performed on 16 patients indicated for bilateral mandibular extractions. A total of 45 teeth were extracted. Rapidity of onset was determined by the absence of pain during gingival separation, while profoundness was measured using a subjective scale of good, fair, and poor depending on the outcome of the procedure. The patients were then asked which technique provided less discomfort. As expected, anesthesia using the inferior alveolar nerve block was obtained within 305 minutes, while the onset of action for the intraligamentary technique was immediate. Of the 21 teeth extracted using the inferior alveolar nerve block, 85.7% were removed painlessly. Only 50% of the 24 teeth extracted using the intraligamentary injection were removed without discomfort. With regards to patient preference, both techniques yielded equal results. The difference in profoundness between the two techniques were subjected to chi-square analysis. This revealed that there is a significant difference in profoundness of anesthesia obtained between the two techniques, with the intraligamentary technique being less profound than the inferior alveolar nerve block.